Hypothermia cannot ameliorate renal fibrosis after asphyxia in the newborn piglet. Issue 1 (9th April 2022) - Wakabayashi, Takayuki; Nakamura, Shinji; Nakao, Yasuhiro; Yamato, Satoshi; Htun, Yinmon; Mitsuie, Tsutomu; Morimoto, Aya; Arioka, Makoto; Koyano, Kosuke; Konishi, Yukihiko; Miki, Takanori; Ueno, Masaki; et al.
Abstract: Background: The effects of therapeutic hypothermia (TH) on renal function are not widely reported, especially in longer term animal models. The hypothesis of this study was that TH of the kidneys of hypoxic–ischemic newborn piglets would reduce pathological renal fibrosis. Methods: Twenty‐five newborn piglets obtained within 24 h of birth were classified into a control group ( n  = 5), an hypoxic insult with normothermia (HI‐NT) group ( n  = 12), and an hypoxic insult with TH (HI‐TH) group (33.5 °C ± 0.5 °C for 24 h; n  = 8). Five days after the insult, all piglets were sacrificed under deep anesthesia by isoflurane inhalation. The kidneys were perfused with phosphate‐buffered paraformaldehyde and immersed in formalin buffer. Territory fibrosis was studied and scored in the renal medulla using Azan staining. Results: Fibrosis area scores (means ± standard deviations) based on Azan staining were 1.00 ± 0.46 in the control group, 2.85 ± 0.93 in the HI‐NT group, and 3.58 ± 1.14 in the HI‐TH group. The fibrosis area of the HI‐NT and HI‐TH groups was larger than that of the control. The HI‐NT and HI‐TH groups were not statistically different. Conclusions: Renal fibrosis is affected by perinatal asphyxia and cannot be prevented by TH, based on histopathological findings.